12th Class Mathematics Continuity and Differentiability

  • question_answer 113) If y = A emx + B enx, show that  

    Answer:

    y = Aemx + Benx                            L.H.S. = y2? (m+n)y1 + mny          = m2 Aemx + n2 B enx ? (m+n) (mA emx + n Benx) + mn          (A enx + Benx)          = m2 Aemx + n2B enx ? m2A emx ? mn Benx ? mnAenx          ? n2 Benx + mn Aemx + Mn Benx = 0                       Hence the result.  


You need to login to perform this action.
You will be redirected in 3 sec spinner

Free
Videos